Woman and the World (1925–1941) Between the Modern and the New Woman: the Ambivalence of Illustrated Women’s (Fashion) Magazine (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
By positioning the place of illustrated magazine Woman and the World (1925–1941) into the frame of feminist counter-public formed in the Kingdom of Serbs, Croats and Slovenes / Yugoslavia, the paper describes the ambivalence in the treatment of women’s emancipation: the ambivalence which is important characteristics of the ideology of moderate bourgeois feminism and of the periodicals which were the expression and constituent of this ideology. The same ambivalence is embodied in its core ideologeme, the modern woman: it defines woman as emancipated in terms of education and public activism but ‘limited’ with marriage, maternity and femininity. However, in particular articles, Woman and the World would accept radical feminist construction of the new woman. Moreover, the semantics of illustrated magazine is by definition complex and ambivalent in respect of fact that visual elements play as important role as textual. The inter-textual relations in magazine increase the possibility of ambivalent (editor’s) encoding and (readers’) decoding of magazine’s meanings. Thus, the meanings of Woman and the World constantly switch between opposing discourses.
Keywords: Woman and the World (1925–1941); moderate bourgeois feminism; the modern woman; the new woman; semantic ambivalence